Library Human Resources Training Through Online-Based Service Provider Platform - Ashary, Muhammad Islah Addaulah; Komara, Diemas Arya (Universitas Pendidikan Indonesia, 2022)
Almost all aspects of life, the need for diverse human resources in modern times makes institutions and human resources, in this case, human resources, design and carry out HR training to improve library capabilities so that they can provide the best service to their students' user. The purpose of this study is to find out how library HR training can be carried out by utilizing online-based service provider platforms, as we know that with a variety of new capabilities and technological developments, creating a remote training system that is efficient and easily accessible by anyone. The research method is a qualitative approach and literature study using related literature in library studies by finding scientific literature. The results of the study indicate that the use of LMS and online training platforms is a positive thing to be used as a choice for HR training of an institution with the selection of training tailored to the needs and desires of the HR who will participate.